Hot books in the Cold War : - Alfred A. Reisch. (Central European University Press, 2013)
Origins, objectives, and launching of the book project under Sam Walker -- Titles, contents, numbers, targets, and aims of the mailings -- The man in the grey suit : George C. Minden and his concept of cultural and ideological competition -- The New York Book Center : books, books, and more books -- The book project reaches new heights : the golden age of the 1960s -- Western and Émigré books and periodicals published with covert support -- New opportunities through East-West contacts -- The early 1970s : the international advisory council -- A lasting enemy -- The communist regimes on the defensive : criticisms, warnings, and attacks -- The person-to-person distribution program : a direct way to reach East Europeans, the early Polish program 1958-1959 -- Another vehicle for reaching the people of eastern Europe : the person-to-person distribution program and personalized mailings -- The most important book distribution point : Vienna -- Letters from Poland, the crucial country -- Letters from Czechoslovakia before and after 1968 -- Letters from Hungary under goulash communism -- Letters from Romania under the Ceausescu regime -- Letters from Bulgaria despite very strict censorship -- The last seventeen years : International Literary Centre, Ltd., East Europe, and the USSR.